2016
DOI: 10.1108/pr-05-2015-0118
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and social identity as predictors of team climate, perceived quality of care, burnout and turnover intention among nurses

Abstract: Purpose The purpose of this paper is to examine the role of transformational leadership (TL) in developing social identity and its subsequent impact on team climate, intention to leave, burnout and quality of patient care among nurses. Design/methodology/approach Data for this cross-sectional study were collected from a sample of 201 registered nurses in Australia through questionnaires. Structural equation modelling was used to test the hypotheses. Findings Results illustrate that social identification ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 91 publications
(123 reference statements)
4
76
0
4
Order By: Relevance
“…On the other hand, institutions that invest in leaders' training and support, can positively influence their employees, improve productivity and motivate them constructively. (7,19) Situations opposed to this type of relationship may be linked to weaker institutional support for the formation of leaders, which opens space for authoritarian and vertical management. This is strongly influenced by traditional management models that are still common in many organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, institutions that invest in leaders' training and support, can positively influence their employees, improve productivity and motivate them constructively. (7,19) Situations opposed to this type of relationship may be linked to weaker institutional support for the formation of leaders, which opens space for authoritarian and vertical management. This is strongly influenced by traditional management models that are still common in many organizations.…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential that nurses engage with transformational leadership in order to improve team satisfaction, ensure a harmonious working environment that can strengthen clinical vision, and improve care delivery. (4,17,19) Transformational leadership is one of the styles that best matches the needs of an organization by enabling employees' voluntary mobilization without causing pressure or anxiety, and achieving the stated purpose. In the case of Nursing, this means meeting the health needs of the population through an efficient care management.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have consistently found that transformational leadership (and its subdimensions) fosters higher levels of team innovation climate (Eisenbeiss et al, 2008;Jaiswal & Dhar, 2015;Pirola-Merlo, Hartel, Mann, & Hirst, 2002;Sun, Xu, & Shang, 2014). In addition, recent work has found that the employee's social identity mediates the transformational leadership/team innovation climate relationship (Cheng, Bartram, Karimi, & Leggat, 2016). Researchers have also begun to examine the specific circumstances in which transformational leadership is related to team innovation climate.…”
Section: Antecedents Of Innovation Climate Leadershipmentioning
confidence: 99%
“…As such, employees’ collective selves will be invoked, transcending their self‐concepts and relating them to the organization (Cheng et al. ).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…With collaborative HRM practices such as recruiting team-oriented candidates, promoting employees based on ability to work with others, providing teamwork training, fostering group incentives, and encouraging cross-departmental communication, employees can absorb the shared norms that emphasize collectivism. As such, employees' collective selves will be invoked, transcending their self-concepts and relating them to the organization (Cheng et al 2016).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%